Editorial - Hadravová, Tereza (Iluminace, 2011)
Introduction to the following series of articles on the relationship between film and neuroaesthetics. Basic overview of the issues and the main ideas of each contribution.
Keywords: science and film; perception; film aesthetics; psychology and film; film psychology